ACE2 modulates glucose homeostasis through GABA signaling during metabolic stress. Issue 3 (September 2020) - Ma, Xiaoyi; Gao, Fei; Chen, Qi; Xuan, Xiuping; Wang, Ying; Deng, Hongjun; Yang, Fengying; Yuan, Li
Abstract : The angiotensin-converting enzyme 2 (ACE2)/angiotensin 1–7 (A1–7)/MAS axis and glutamate decarboxylase 67 (GAD67)/gamma-aminobutyric acid (GABA) signal both exist in the islet and play important roles in regulating blood glucose metabolism. It has been reported that the activation of ACE2 in the brain increases GABA expression to improve biological effects; however, it is unclear whether there is functional correlation between the ACE2/A1–7/MAS axis and GAD67/GABA signal in the islet. In this study, we showed that the ACE2/A1–7/MAS and GABA signaling systems decreased in the islet of different metabolic stress models. In ACE2-knockout mice, we found that GAD67 and GABA expression decreased significantly, which was reversed by exogenous administration of A1–7. Furthermore, A1–7 mediated PDX1 and AKT activation was inhibited by allylglycine (a specific GAD67 inhibitor) in MIN6 cells. Moreover, giving A1–7 and GABA could significantly reduce beta-cell dedifferentiation and improved glucose metabolism during metabolic stress in vivo and in vitro . In conclusion, our study reveals that the ACE2/A1–7/MAS axis improves beta-cell function through regulating GAD67/GABA signal in beta cells and that up-regulating the ACE2/A1–7/MAS axis and GABA signals delays the development of obesity-induced diabetes.